Pengaruh Pengalaman Kerja, Iklim Kerja dan Kemampuan Kerja Terhadap Pengembangan Karir di Kantor Pelayanan Pajak Pratama Pematang Siantar - Siregar, Nurul Khadijah; Napitupulu, Iwan Kristoni; Handayani, Putri; Situmorang, Beringin Raja; Depari, Emenda Tinalyta; Pane, Sri Gustina; Safrida, Safrida; Wasesa, Supar (Journal of Management and Economics Research, 2024)
This study aims to determine the Effect of work experience, working climate and work ability appraisal partially and simultaneously on the career development in the Kantor Pelayanan Pajak Pratama Pematang Siantar. The study was conducted at the Kantor Pelayanan Pajak Pratama Pematang Siantar Jalan Dahlia Nomor 12, Simarito, Kecamatan Siantar Barat, Kota Pematang Siantar, Provinsi Sumatera Utara, kode pos 21111, with a population of 108 people, and a study sample. of 52 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained work experience has a effect on the career development of the Kantor Pelayanan Pajak Pratama Pematang Siantar, this is supported by the results of t count analysis > t-table (3,668 > 2,011) at n = 52 at 95% significance level. Working climate has a not effect on the career development of the Kantor Pelayanan Pajak Pratama Pematang Siantar, this is supported by an analysis of t count < t-table (0,552 < 2,011) at n = 52 at 95% significance level. Work ability appraisal has a effect on the career development of the Kantor Pelayanan Pajak Pratama Pematang Siantar, this is supported by an analysis of t count > -table (2,170 > 2,011) at n = 52 with a significant level of 95%.Value of F-count> F table (25,500 > 2,80) This states that together (multiple) there are positive and significant effects of work experience, working climate and work ability appraisal on the career development of employees of the Kantor Pelayanan Pajak Pratama Pematang Siantar. Thus the hypothesis proposed is accepted by the truth.